Reply to comment on: Carbonaceous matter in ∼3.5 Ga black bedded barite from the Dresser Formation (Pilbara Craton, Western Australia) – Insights into organic cycling on the juvenile earth - L. Weimann; M. Reinhardt; J.-P. Duda; H. Mißbach-Karmrodt; H. Drake; J. Schönig; J. Holburg; L.B. Andreas; J. Reitner; M.J. Whitehouse; V. Thiel (Precambrian Research, 2024)

Carbonaceous matter in ∼ 3.5 Ga black bedded barite from the Dresser Formation (Pilbara Craton, Western Australia) – Insights into organic cycling on the juvenile Earth - L. Weimann; M. Reinhardt; J.-P. Duda; H. Mißbach-Karmrodt; H. Drake; J. Schönig; J. Holburg; L.B. Andreas; J. Reitner; M.J. Whitehouse; V. Thiel (Precambrian Research, 2024)

Aspects of the biological carbon cycle in a ca. 3.42-billion-year-old marine ecosystem - M. Reinhardt; V. Thiel; J.-P. Duda; A. Hofmann; D. Bajnai; W. Goetz; A. Pack; J. Reitner; M. Schanofski; J. Schönig; M.J. Whitehouse; H. Drake (Precambrian Research, 2024)

Molecular fossils in reefal carbonates and sponges of the deep fore reef of Mayotte and Mohéli, Comoro Islands, western Indian Ocean - Joely Marie Maak; Daniel Birgel; Joachim Reitner; Eberhard Gischler; Wolf-Christian Dullo; William J. Foster; Jörn Peckmann (Facies, 2024)
Microbial carbonates are common components of Quaternary tropical coral reefs. Previous studies revealed that sulfate-reducing bacteria trigger microbial carbonate precipitation in supposedly cryptic reef environments. Here, using petrography, lipid biomarker analysis, and stable isotope data, we aim to understand the formation mechanism of microbial carbonate enclosed in deep fore reef limestones from Mayotte and Mohéli, Comoro Islands, which differ from other reefal microbial carbonates in that they contain less microbial carbonate and are dominated by numerous sponges. To discern sponge-derived lipids from lipids enclosed in microbial carbonate, lipid biomarker inventories of diverse sponges from the Mayotte and Mohéli reef systems were examined. Abundant peloidal, laminated, and clotted textures point to a microbial origin of the authigenic carbonates, which is supported by ample amounts of mono- O -alkyl glycerol monoethers (MAGEs) and terminally branched fatty acids; both groups of compounds are attributed to sulfate-reducing bacteria. Sponges revealed a greater variety of alkyl chains in MAGEs, including new, previously unknown, mid-chain monomethyl- and dimethyl-branched MAGEs, suggesting a diverse community of sulfate reducers different from the sulfate-reducers favoring microbialite formation. Aside from biomarkers specific for sulfate-reducing bacteria, lipids attributed to demosponges (i.e., demospongic acids) are also present in some of the sponges and the reefal carbonates. Fatty acids attributed to demosponges show a higher diversity and a higher proportion in microbial carbonate compared to sponge tissue. Such pattern reflects significant taphonomic bias associated with the preservation of demospongic acids, with preservation apparently favored by carbonate authigenesis.

A relict oasis of living deep-sea mussels Bathymodiolus and microbial-mediated seep carbonates at newly-discovered active cold seeps in the Gulf of Cádiz, NE Atlantic Ocean - Luis Somoza; José Luis Rueda; Francisco J. González; Blanca Rincón-Tomás; Teresa Medialdea; Olga Sánchez-Guillamón; Michael Hoppert; Juan T. Vázquez; Pedro Madureira; Esther Santofimia; Enrique López-Pamo; Desirée Palomino; et al. (PalZ, 2021)
Extensive beds of the deep-sea mussel Bathymodiolus mauritanicus (currently also known as Gigantidas mauritanicus ) linked to active cold seeps related to fissure-like activity on Al Gacel mud volcano, Gulf of Cádiz, were filmed and sampled for the first time during the oceanographic expedition SUBVENT-2 aboard R/V Sarmiento de Gamboa. Al Gacel mud volcano is one of up to 80 fluid venting submarine structures (mud volcanoes and mud volcano/diapir complexes) identified in the Gulf of Cádiz as result of explosive venting of hydrocarbon-enriched fluids sourced from deep seated reservoirs. This mud volcano is a cone-shaped edifice, 107 m high, 944 m in diameter constituted by mud breccias and, partially covered by pavements of seep carbonates. Extensive beds of this deep-sea mussel were detected at the northern flank at 810–815 m water depth associated with bacterial mats around intermittent buoyant vertical bubble methane plumes. High methane concentrations were measured in the water column above living mussel beds. Other chemosymbiotic species ( Siboglinum sp., Solemya elarraichensis , Isorropodon sp., Thyasira vulcolutre and Lucinoma asapheus ) were also found in different parts of Al Gacel mud volcano. Al Gacel mud volcano may currently represent one of the most active mud volcanoes in the Gulf of Cádiz, delivering significant amounts of thermogenic hydrocarbon fluids which contribute to foster the extensive chemosynthesis-based communities detected. This finding is of paramount importance for linking extremophile bivalve populations along the North Atlantic, including cold seeps of the Gulf of México, hydrothermal vents of the Mid-Atlantic Ridge and now, detailed documented at the Gulf of Cádiz.

Spatial patterns in the distribution of benthic assemblages across a large depth gradient in the Coral Sea, Australia - Robin J. Beaman; Tom C. L. Bridge; Carsten Lüter; Joachim Reitner; Gert Wörheide (Marine Biodiversity, 2016)

Erratum to: Precious coral and rock sponge gardens on the deep aphotic fore-reef of Osprey Reef (Coral Sea, Australia) - G. Wörheide; S. Vargas; C. Lüter; J. Reitner (Coral Reefs, 2012)

Respiratory Chain Complex-I Defect Mimicking Myasthenia - J. Finsterer; I. Oberman; A. Reitner (Metabolic Brain Disease, 2002)

Sponge–microbe associations and their importance for sponge bioprocess engineering - Ronald Osinga; Evelyn Armstrong; J. Grant Burgess; Friederike Hoffmann; Joachim Reitner; Gabriela Schumann-Kindel (Hydrobiologia, 2001)

Contrasting effects of solar radiation on dissolved organic matter and its bioavailability to marine bacterioplankton - Ingrid Obernosterer; Bettina Reitner; Gerhard J. Herndl (Limnology and Oceanography, 1999)
The effect of ultraviolet radiation on the bioavailability of dissolved organic matter (DOM) to marine bacterioplankton was investigated in the Mediterranean Sea (Strait of Gibraltar, South and North Aegean Sea) and in the Caribbean Sea off Curacao. Surface‐water samples (collected between 1 and 85 m in depth) exposed to solar radiation did not show a distinct pattern in subsequent bacterial growth. However, samples collected from a pronounced chlorophyll maximum (two stations in the Strait of Gibraltar and four stations in the Aegean Sea) displayed in a 50% lower bacterial activity in the radiation‐exposed treatments compared with the dark controls. In contrast, mesopelagic water samples (200–350 m in depth) exposed to surface solar radiation exhibited a two‐ to fourfold increase in bacterial activity compared with the corresponding dark controls. Addition of the model protein bovine serum albumin (BSA) to mesopelagic‐water samples and subsequent exposure to solar radiation resulted in a 50% lower rate of bacterial activity compared with the dark treatments, thus indicating the occurrence of photochemically induced changes to this labile compound. This decrease in bacterial activity in BSA‐amended, irradiated water was also detectable in surface waters sampled off Curaçao, whereas BSA amendment to surface water from the Mediterranean Sea did not result in a distinct pattern of bacterial activity. Our data indicate that exposure of DOM to solar radiation causes a reduced bioavailability of the exposed DOM to bacterioplankton, if the bacterial activity : dissolved organic carbon (DOC) concentration ratio is high (indicative of labile DOM). If the bacterial activity:DOC ratio is low (indicative of more refractory DOM), the bioavailability of the DOM is increased upon exposure to solar radiation.

Cold seep deposits of Beauvoisin (Oxfordian; southeastern France) and Marmorito (Miocene; northern Italy): microbially induced authigenic carbonates - J. Peckmann; V. Thiel; W. Michaelis; P. Clari; C. Gaillard; L. Martire; J. Reitner (International Journal of Earth Sciences, 1999)

Microbial activity under the ice cover of the shallow Neusiedler See (Austria, Central Europe) - Bettina Reitner; Alois Herzig; Gerhard J. Herndl (Hydrobiologia, 1997)

Role of ultraviolet‐B radiation on photochemical and microbial oxygen consumption in a humic‐rich shallow lake - Bettina Reitner; Gerhard J. Herndl; Alois Herzig (Limnology and Oceanography, 1997)
In a humic‐rich, shallow lake (Lake Neusiedl), the seasonal dynamics of the humic and the nonhumic dissolved organic carbon (DOC) were investigated and the photochemical oxygen consumption rates of these DOC fractions exposed to surface solar radiation levels were compared with that of the bulk DOC and bacterial respiration. Furthermore, bacterial utilization of the humic, nonhumic, and bulk DOC pre‐exposed to solar radiation was compared with utilization of the different fractions of DOC held in the dark prior to inoculating natural bacterial assemblages. The concentration of the unfractionated DOC pool ranged from ∼3 mmol C liter −1 during summer to 1.3 mmol C liter −1 in late spring. The mean contribution of humic DOC was 35.2% of bulk DOC. Under the full spectrum of solar radiation, photochemical oxygen consumption of the unfractionated DOC was 3.3 µ mol O 2 liter −1 h −1 , 1.8 µ mol O 2 liter −1 h −1 of the humic DOC, and 1.7 µ mol O 2 liter −1 h −1 of the nonhumic DOC. In the absence of UVB, photochemical oxygen consumption was reduced by 35% in the unfractionated DOC, 38% in the humic, and 27.5% in the nonhumic DOC. Under the full spectrum of solar radiation, the photochemical oxygen consumption normalized to DOC was more than twice as high (2.83 µ mol O 2 mmol −1 C h −1 ) for humic than for nonhumic DOC. The bacterial oxygen consumption rate was ∼30% of the photochemical oxygen consumption of the unfractionated DOC. In batch culture experiments with natural bacterial assemblages as inocula, the bacterial yield was generally higher with substrate exposed to the full spectrum of solar radiation than with substrate held in the dark prior to inoculation. Exposure of 0.8‐ µ m filtered water to the full spectrum of surface solar radiation for 2–3 h resulted in a decline in activity (measured by thymidine incorporation) to 47% of the activity measured in the dark. If UVB was excluded, bacterial activity was 62% of that in the dark. Subsequent incubation at 5–20‐cm depth under in situ radiation for another 2–3 h resulted in bacterial activity similar to that detected in the dark incubations at the surface. Bacteria exposed to the full range of solar radiation at the surface and incubated subsequently in the dark exhibited significantly lower activity than bacteria exposed to in situ solar radiation in distinct depth layers. This result indicates that bacteria rapidly recover from previous UV stress in the absence of UVB. Based on our results, we estimate that the photooxidation‐mediated residence times in the top 5‐cm layer of the water column are 90 and 45.5 d for the nonhumic and humic fractions and 75 d for unfractionated DOC. For the entire water column, ∼10% of the remineralization activity (bacterial respiration + photochemical oxygen consumption) is due to photooxidation of the DOC, and the mean residence time of DOC is ∼80 d.

Role of ultraviolet-B radiation on bacterioplankton and the availability of dissolved organic matter - Gerhard J. Herndl; Albert Brugger; Silvia Hager; Edith Kaiser; Ingrid Obernosterer; Bettina Reitner; Doris Slezak (Plant Ecology, 1997)